EFFECT OF OZONE ENRICHMENT AND SPRAYING WITH ORGANIC NUTRIENT ON NUTRIENT AND WATER USE EFFICIENCY AND FERTILIZER PRODUCTIVITY OF BROCCOLI PLANT CULTIVATED HYDROPONICALLY WITH MODIFIED NFT TECHNOLOGY. - Salman, A. D.; Abdulrasool, I. J. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2022)
This study was carried out at University of Baghdad - College of Agricultural Engineering Sciences - research station B during the fall season of 2019-2020, in order to evaluate the effect of Ozone enrichment and the foliar application of organic nutrient  on nutrient and water use efficiency and fertilizer productivity of broccoli plant using the modified NFT film technology. A factorial experiment (2*5) was carried out within Nested Design with three replicates. The ozone treatment was distributed into the main plots which consisted of oxygen (O2) and ozone (O3). The foliar application of organic nutrients were distributed randomly within each replicate including five treatments, which were the control treatment (T0), Coconut water with two concentrations of 50 (T1) and 100 ml. L-1 (T2), and Moringa leaves extract at two concentrations 2% (T3) and 4% T4. Results revealed a significant effect of ozone and the foliar application of coconut water 100 ml. L-1 at the treatment of O3T2 on the leaves content of N, P, and K, and vegetative dry weight, vegetative to roots dry weight ratio, the recovering efficiency of N, P, k, the use efficiency of N, P, K, and fertilizer productivity, reaching 4.530, 0.674, 3.139%, 178.81 g. Plant-1, 5.74, 8.21, 8.29, 8.68%, 65.17, 36.35, 24.48%, and 3.616 kg yield. Kg fertilizer, respectively, compared to the control treatment (O2T0). The treatment of ozone enrichment and the foliar application of 2% Moringa leaf extract (O3T3) or with coconut water 100 ml. L-1 (O3T2) gave a significant increment in plant yield reached 919.33 and 917.00 g. Plant-1 (O2T0) which gave the lowest plant yield reached 624.00 g. Plant-1.